Medicinal plant trade and opportunities for sustainable management in the Cape Peninsula, South Africa - Loundou, Paul-Marie (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScConsEcol (Conservation Ecology and Entomology))--Stellenbosch University, 2008.